Pembelajaran Matematika Menggunakan Media Audio Visual Pada Masa Pandemi Covid-19 - Firda Halawati (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
This study aims to (1) find out how to learn mathematics during the covid-19 pandemic (2) find out how to learn mathematics using audio-visual media during the covid-19 pandemic. The approach used in this research is descriptive qualitative. Sources of data used in this study include primary sources, namely the results of interviews with as many as 6 educators and students and secondary sources in the form of journals and books. This data collection is done by conducting interviews, observations, and documentation. The results of the study show that (1) the learning process generally runs smoothly, it can be seen from the limited face-to-face learning in utilizing the use of learning media, especially in learning mathematics. In addition to limited face-to-face meetings, the rest of the learning is done online. (2) the use of audio-visual media in learning mathematics during the covid-19 pandemic is divided into three categories, namely; audio media, visual media and audio-visual media. The use of audio media to emphasize or explain the material and to optimize the auditory abilities of students. The use of visual media is not maximized in the learning process, due to the lack of explanations related to the material that has been given. Meanwhile, the use of audio-visual media, both available through YouTube and recorded by the educators themselves, is briefly intended so that students can repeat the videos they have seen and heard, thus clarifying learning when students have difficulty understanding the material being studied in this case on mathematics learning.